2009
DOI: 10.1016/j.eurpsy.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a case group concept for inpatients with mental disorders in Germany: Using self-report and expert-rated instruments

Abstract: The aim of this study was to evaluate a case-mix system to classify inpatients with mental disorders in Germany by means of self-report and expert-rated instruments. The use of case-mix systems enhances the transparency of performance and cost structure and can thus improve the quality of mental health care. We analysed a consecutive sample of 1677 inpatients with mental disorders from 11 hospitals using regression tree analysis. The model assigns patients to 17 groups, accounting for 17% of the variance for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…It is routinely applied in many countries (e.g., Denmark, Nova Scotia, Italy, Australia) in the treatment of patients with mental disorders (Bech et al, 2003;Kisely, Campbell, Crossman, Gleich, & Campbell, 2007;Lora et al, 2001;Trauer et al, 1999) and is gaining increasing relevance in the framework of the development of case group systems (Andreas et al, 2009;Buckingham, Burgess, Solomon, Pirkis, & Eagar, 1998;Gaines et al, 2003). In line with international developments and due to the lack of suitable national clinician-rating instruments for the differential assessment of severity, the HoNOS was translated into German with authorization from the test authors.…”
Section: Introductionmentioning
confidence: 97%
“…It is routinely applied in many countries (e.g., Denmark, Nova Scotia, Italy, Australia) in the treatment of patients with mental disorders (Bech et al, 2003;Kisely, Campbell, Crossman, Gleich, & Campbell, 2007;Lora et al, 2001;Trauer et al, 1999) and is gaining increasing relevance in the framework of the development of case group systems (Andreas et al, 2009;Buckingham, Burgess, Solomon, Pirkis, & Eagar, 1998;Gaines et al, 2003). In line with international developments and due to the lack of suitable national clinician-rating instruments for the differential assessment of severity, the HoNOS was translated into German with authorization from the test authors.…”
Section: Introductionmentioning
confidence: 97%
“…More specifically, several studies utilizing DRGs for the prediction of LOSs reported that DRGs explained, at most, 20-30% of the variance in LOSs [14,15] and explained less than 10% of the variance on average [16][17][18]. Therefore, data in addition to LOS, including clinical information, need to be employed when using DRGs as an assessment tool for psychiatric care [14]. Previous findings related to admission type, prevalence of coercive admissions, and relationship to LOS [19][20][21] have relied on the subjective experiences of patients who experienced coercive admissions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, DRGs were used as a weighted index for the comparison of LOSs in psychiatric and other units [13]. More specifically, several studies utilizing DRGs for the prediction of LOSs reported that DRGs explained, at most, 20-30% of the variance in LOSs [14,15] and explained less than 10% of the variance on average [16][17][18]. Therefore, data in addition to LOS, including clinical information, need to be employed when using DRGs as an assessment tool for psychiatric care [14].…”
Section: Introductionmentioning
confidence: 99%
“…Empirische Befunde dazu zeigen auf, dass die Auspr ä gung des Schweregrades in den aufgef ü hrten Problembereichen nur ein Merkmal zur Varianzaufkl ä rung der Behandlungsdauer. So konnten Andreas et al [31] aufzeigen, dass auch die Diagnose zu Beginn, das Alter der Patienten, die Erkrankungsdauer, die Auspr ä gung interpersoneller Probleme, Komorbidit ä ten (somatisch und psychisch), gesundheitsbezogene Lebensqualit ä t, Partnersituation und Berufsstatus der Patienten wichtige Pr ä diktoren der Behandlungsdauer in station ä rer psychosomatischer / psychotherapeutischer Rehabilitationsbehandlung sind. Auch f ü r die station ä re Rehabilitationsbehandlung Suchtkranker stellt die Auspr ä gung des Schweregrades in funktionalen, sozialen und umweltbezogenen Problembereichen nur ein Pr ä diktor des Ressourcenverbrauchs dar.…”
Section: Instrumenteunclassified